2014
DOI: 10.2298/abs1402801p
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells as key players in periodontal disease

Abstract: Mast cell (MC) active mediators promote inflammation through changes induced in the connective tissue components of human gingiva. The aim of this study was to evaluate the distribution, mast cell density and their relationship with the degree of inflammatory infiltrate in gingiva from patients with periodontal disease. Thirty-nine cases with periodontal disease and 12 cases without significant changes to the gingival mucosa were investigated. MCs were identified on paraffin-embedded specimens by immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…In our material, MCs were found neither in epithelium of healthy gingiva, nor in gingivitis, but in some samples of moderate to advanced periodontal disease they were found in oral epithelium. Similar results were recently published by Popovici et al 16 . These authors found that the number of intraepithelial MCs increases with the severity of inflammation and intraepithelial MCs could be important in the evaluation of the severity of periodontal disease.…”
Section: Discussionsupporting
confidence: 93%
“…In our material, MCs were found neither in epithelium of healthy gingiva, nor in gingivitis, but in some samples of moderate to advanced periodontal disease they were found in oral epithelium. Similar results were recently published by Popovici et al 16 . These authors found that the number of intraepithelial MCs increases with the severity of inflammation and intraepithelial MCs could be important in the evaluation of the severity of periodontal disease.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, an increased amount of IL 1beta, IL 4, IL-6, TNF-alpha and IFN gamma was observed. Cytokine production is involved in the recruitment of Langerhans cells and clonal expansion of cytotoxic T cells [10,13].…”
mentioning
confidence: 99%
“…Mast cells in periodontal disease were studied by a number of researchers and often different results were obtained because they used variable mast cell counting methods and the insufficient number of samples. [ 5 9 18 ]…”
Section: Discussionmentioning
confidence: 99%